The migrant crisis in the Mediterranean Sea: Empirical evidence on policy interventions. (December 2021) - Amenta, Carlo; Di Betta, Paolo; Ferrara, Calogero
Abstract: This paper presents a novel set of empirical evidence to explore several hypotheses regarding the migrant crisis in the Mediterranean Sea. The political instability in transit countries, such as Libya, that made pre-existent repatriation policies ineffective, called for several search-and-rescue operations in the Mediterranean, which in turn have been wrongly accused of fostering illegal immigration and increasing deaths at sea. The empirical results show that the main determinants of the departures are several root causes at the departing African countries, underlining the importance of fighting human smuggling networks. The paper suggests a change in migration studies' perspective, to leave behind the pull-and-push-factors narrative that is open to be politically slanted and to focus instead on the short-term versus long-term horizons of implementation of the policy interventions. Highlights: The pull-and-push-factors narrative on the migrant crisis in the Mediterranean Sea allows policymakers to slant the policies. The policies should be characterized as short-term or long-term to avoid the risk of being politically slanted. The search-and-rescue operations in the Central Mediterranean route are not pull factors and do not increase deaths at sea. The departures depend on several root causes at the originating African countries and on the presence of human smuggling networks. The departures also depend on the political instability of transit countries such, as Libya.